Macroeconomic factors affecting exchange rate fluctuation: Markov switching Bayesian quantile approach - Tungtrakul T. (2017)
© 2016 by the Mathematical Association of Thailand. All rights reserved. We employ Markov switching Bayesian Quantile regression (MSBQR) to investigate macroeconomic factors of exchange rate fluctuation in Thailand. The approach allows us to capture the effect of macroeconomic variables on the different levels of exchange rate and also accommodate structural breaks in exchange rate. The results show that the inflation rate has slight effect on the exchange rate, while the effect is greater in the case of the bond yield and public debt.